Event report: “Green adaptation strategies for water security in the Central American Dry Corridor”. Nicoya, Costa Rica. - Stefan, Catalin (2019)
Digital report Co-organized by: Mesoamerican Center of Sustainable Development of the Dry Tropics (CEMEDE) and the Water Resources Center for Central America and The Caribbean (HIDROCEC) of the National University of Costa Rica (UNA). Research Group INOWAS at the Department of Hydrosciences of the Technische Universität Dresden (TUD), Germany